If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2y + -1) + -6(y + -2) + 3 = 6 Reorder the terms: 5(-1 + 2y) + -6(y + -2) + 3 = 6 (-1 * 5 + 2y * 5) + -6(y + -2) + 3 = 6 (-5 + 10y) + -6(y + -2) + 3 = 6 Reorder the terms: -5 + 10y + -6(-2 + y) + 3 = 6 -5 + 10y + (-2 * -6 + y * -6) + 3 = 6 -5 + 10y + (12 + -6y) + 3 = 6 Reorder the terms: -5 + 12 + 3 + 10y + -6y = 6 Combine like terms: -5 + 12 = 7 7 + 3 + 10y + -6y = 6 Combine like terms: 7 + 3 = 10 10 + 10y + -6y = 6 Combine like terms: 10y + -6y = 4y 10 + 4y = 6 Solving 10 + 4y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 4y = 6 + -10 Combine like terms: 10 + -10 = 0 0 + 4y = 6 + -10 4y = 6 + -10 Combine like terms: 6 + -10 = -4 4y = -4 Divide each side by '4'. y = -1 Simplifying y = -1
| -0.2(.12-h)=8.6 | | -5/6y-3/4 | | 4+(y+3)=19 | | 20x^2+33x+14=0 | | 18x^3-15x^2-9x=0 | | t^2-64/121 | | 25x^2-15xy+2y=0 | | m-10/6=1/5 | | X*cosx=0 | | -11x+2x^2-13=0 | | 4x-5=2(2-u)-3 | | (2x-6)+4(x+3)= | | 6+4x+3-2x=4+4x+5-3x | | 2/3y=26 | | 5.3=u | | 50=sqrt(3x) | | 4a-7a+10-15= | | tanx=-0.5x | | 2x+21+3x-4=55-3x+34 | | 22=4u-6 | | m/6=20 | | F(x)=36x^3+51x^2-42x-45 | | f(x)=3x^2+12x-7 | | 45-1.75n=2.25n-11 | | 3x+7y=c | | 1.5(x-5)=9.6 | | 5x^2-42x+27=0 | | 12(5+3x)=240 | | 4x+4=12-x | | (-2x^2)-x+2=0 | | Z=-3x+3y+5 | | 25n^2-24n+16=0 |